Measuring The Amount Of Ammonia Gas In Cattle Using The MQ137 Sensor In Rawan Village, Mayang District, And Member District With The Goal Of Raising Public Health Standards - Misto; Tri Mulyono; Imam Rofi’i; Arry Yuariatun Nurhayati; Yuda Cahyoargo Hariadi; Linggar Ayu Octaviani (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
The majority of the farmers in Pringtali Hamlet, Mayang Village, Jember Regency, are also cattle breeders. Cattle breeders make up the majority of farmers. They construct basic cow enclosures; the majority are joined to the home, while others are independent. For the two of them, the cage's quality does not match the standards for cleanliness. Even in cages attached to the home, the smell of cow poo can be detected up to three meters outside the cage and within the main house. Ammonia is often the gas that is released from either liquid or solid cow manure. This gas can have some negative effects on health; in fact, it can irritate respiratory blood vessels in those 60 years of age and older. Because ammonia gas from cages has not been handled adequately, the living environment is contaminated. The goal of our service is to measure the threshold level of ammonia gas surrounding the cage (using the MQ-135 sensor) in order to ascertain whether the cage is ecologically friendly and healthy. Two cow pens one adjacent to a domestic main house in Pringtali Hamlet and the other from a separate traditional pen have had measurements taken. By monitoring liquid excrement drainage channels and promoting air circulation around the cage, the measurements seek to maintain the cleanliness of the cage environment and the management of ammonia gas content. Cage management so that the livestock community can improve the cleanliness of the living environment.